Clinical and morphological variants of hepatitis onset with congenital cytomegalovirus and hepatitis C infection - R. A. Ushakova; O. P. Kovtun; I. E. Valamina; N. B. Blinkova; Ya. M. Krohaleva; L. M. Ziguleva; M. A. Shvarts; S. N. Tuponogov; A. M. Nikolaeva (Журнал инфектологии, 2014)
We present comparative analysis of clinical – morphological data from infants with congenital cytomegalovirus and hepatitis C infection. 97 patients with hepatitis underwent a standard set of clinical and laboratory tests. ELISA and PCR were used to verify infectious agents. Informed consent to perform a liver biopsy was obtained from the parents of 28 children. immunohistochemical test of the liver samples managed to identify markers of cytomegalovirus (protein pp65 and p52) and hepatitis C (helicase NS3). The hepatitis C virus was detected in 41 patients: 3a genotype – 68.3%, 1b –31.7% respectively. Congenital hepatitis C onset presents itself as mild and atypical and causes chronic hepatitis with the 1st degree fibrosis. Cytomegalovirus replication markers were found in 56 children. The most common manifestations of hepatitis associated with cytomegalovirus infection are prolonged jaundice, cholestasis, gepatolienalny syndrome, early onset of the disease with increased transaminase levels and dominance in AST. Structural changes of the liver are characterized by the presence of inflammatory infiltration, cholestasis with duktulopenia, lobular structure damage. Congenital cytomegalovirus-related hepatitis is likely to result in liver cirrhosis and is associated with poor prognosis.